Dve fazi baroka v slovenski poeziji - Paternu, Boris (Jezik in slovstvo, 1998)
Two stages of Baroque in Slovenian secular poetry - one exemplified by Anton Feliks Dev (1732-186) - are compared. The analysis focuses on deictic stylization (especially on metaphorical amplifacion) and its transformations from late Baroque (Dev) to classiscts Baroque (Prešeren).
Keywords: Dev, Feliks Anton; Prešeren, France, 1800-1849; Slovene literature; slovenska književnost; slovenska poezija; barok; literarne študije